PEMBANGUNAN PERTANIAN SEBAGAI UPAYA MENINGKATKAN PEREKONOMIAN DI PEDESAAN (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Agriculture becomes major revenues of rural economic in Indonesia. However, more than 50 percent poor people in Indonesia are farmer. In order to increasing rural economic especially to farmer, Indonesian government need to made some stategic plans of agriculture development. Agriculture and rural economic are two things that effects each other. If agriculture production decreasing then rural economic was decreasing too indirectly. In this article, enclose some recommendation to agriculture development in Indonesia. There are agriculture diversifcation, empowerment of farmer itself, developing agriculture technology, and new model of agriculture that is organic farming. Main focus is in deversifcation agriculture so the farmer could get extra incomes from their farming. The most important is the governments should give opportunity and access widely to agriculture sector and farmers.Keywords: Agriculture development, rural economic, farmer’s income